Pulmonary functions in car air conditioner users and non-air conditioner users in tertiary care centre, South Tamilnadu, India - S., Hoshea Jeba Ruth; Vincent, Lisha (International Journal of Research in Medical Sciences, 2019)
Background: Air conditioners are used extensively these days of the modern lifestyle. Inhalation of cold dry air while using Air conditioners causes bronchoconstriction due to which alteration may occur in pulmonary function. This study was aimed to compare the Pulmonary Function tests of Car AC users and non AC users. Methods: The Study included 52 employees not exposed to car air conditioner as a control (group I) and 52 employees exposed to car air conditioner with minimum exposure of 1 hour per day for 6 months as a subject (group II). Pulmonary function tests were performed using computerised spirometer. Statistical analysis was done by unpaired t test. Results: Age, Height and weight are not statistically significant between study group and control group. Forced vital capacity, forced expiratory volume in 1 second, Ratio of Forced vital capacity and Forced expiratory volume in 1 second, Inspiratory reserve volume, Expiratory reserve volume, Maximum voluntary ventilation are decreased in car air conditioner users compared to non-users, but was not significant. Forced expiratory flow (FEF), Peak expiratory flow rate (PEFR) values shows statistically significant decreased in car air conditioner users. Conclusions: The present study shows hyper-responsive airways on exposure to cold air which leads to bronchoconstriction. The significant decrease in PEFR, FEF suggest that upper airways as well as smaller airways are affected on exposure to car AC. So, Exposure to car Air Conditioner leads to risk of developing respiratory dysfunction.